Assessing the Impact of Early Childhood Caries on the Development of First Permanent Molar Decays - Songur, Fatma; Simsek Derelioglu, Sera; Yilmaz, Sinan; Koşan, Zahide (Frontiers in Public Health, 2019)
ABSTRACT Aim: The aim of this study was to evaluate whether the treated and untreated severe early childhood caries (ECC) in children would make any impact on the Permanent First Molar (PFM) decays. Materials and Methods: Our descriptive epidemiological study was conducted in Ataturk University, Faculty of Dentistry, Department of Pediatric Dentistry /Erzurum-Turkey, between 2011-2017. We included a total of 90 children (44 girls, 46 boys), and divided them into 3 equal groups. They were 6-9 years old with a mean age of 7.38 ± 0.89. Group 1 consisted of the patients who had previously been treated under GA, Group 2 included the patients with untreated ECC and with no previous dental treatment, and Group 3 consisted of the patients who had been periodically treated in normal clinical settings. Each patient was processed through; dmft scoring and PFM caries evaluation process in accordance with International Caries Detection and Assessment System (ICDAS), respectively. The obtained data was analyzed with SPSS v20.0. And also, we used One-way ANOVA, Kruskal-Wallis and Mann Whitney U tests. Results: In accordance with ICDAS, we found that Group 3 had the highest mean number of PFMs (2 ± 1.43) and Group 2 had the lowest (1.43 ± 1.45). In Group 2, the number of ICDAS-determined carious PFMs were significantly lower than the other groups (p˂0.05). However, ICDAS score 6 was 0 in Group 1, while it was determined higher as 4.2% in Group 2. Conclusion: In respect to our research outcomes, which revealed that regardless of treated or not severe ECC had a significant impact on the PFMs, we strongly recommend that the parent of the children experiencing ECC should be informed about the risk of future caries in PFMs. Keywords: Early childhood caries, first permanent molar teeth caries, window of infectivity, general anesthesia, ICDAS.